Lag Time dalam Transformasi Sosial Hukum; Mengapa Masyarakat Lambat Beradaptasi dengan Regulasi Baru dalam Era Reformasi - Adinda, Nendena Rizqi; Sulastri, Dewi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This article analyzes the phenomenon of "lag time" or the temporal gap in Indonesia's socio-legal transformation post-1998 Reformation. Lag time is defined as the misalignment between the progressive ambition of law as a tool of social engineering and the reality of adaptation and internalization at the level of societal legal culture. The study employs a juridical-sociological methodology to identify the determinant factors causing the slow acceptance of new regulations. The findings indicate that lag time manifests from the failure to synchronize the structural dimension and the cultural dimension of the legal system. Structural factors include the weak capacity of law enforcement, regulatory inconsistency, and the failure of top-down socialization. Meanwhile, cultural factors encompass the legacy of authoritarian legal culture based on fear, resistance from living law, and public pragmatism. The conclusion urges the necessity of systemic reform that focuses not only on improving the substance of the law but also on transforming the legal culture through participatory education to achieve compliance rooted in ethical awareness and justice. Keywords: Lag Time, Sociology of Law, Legal Culture, Legal Reform.